Spectrometric and electrochemical investigation of vanadium(V) and vanadium(IV) tartrate complexes in solution - Khan,Ahmad R. (2006)
Spectroscopic and electrochemical studies were carried out to characterize the vanadium(IV) and (V) complexes that form in solution and their interconversions. 51V NMR spectroscopy coupled with ¹H NMR, 13C NMR and EPR spectroscopy were used to characterize the vanadium(V)-tartrate complexes that form in the vanadium-tartrate system. The major complex that forms over most of the pH range is a 1:1 complex. In addition a minor 1:2 complex forms. The 1:2 complex formed from enantiomerically pure tartaric acid was less stable than complex formed from racemic tartaric acid. These complexes are different than the 2:2 complex that is the major contributor in the vanadium(IV)-tartrate system. The polarographic and cyclic voltammetic investigations of the electrochemical behavior of V(V) in the presence of tartrate demonstrated a complex formation. The diffusion coefficient values of free vanadium ions and vanadium-tartrate complexes were determined. The minimum average values for the diffusion coefficient for the vanadium(IV)-tartrate 2:2 complexes were determined to range from 3 ´ 10-6 cm² s-1 to 17 ´ 10-6 cm² s-1 depending on pH.